Perencanaan Strategi Korporasi Bidang Pariwisata Pada Injourney (PT Aviasi Pariwisata Indonesia (Persero)) - Gunawan Aji; Ayu Wahyuning Ragil; Mari Patun Hasanah; Naelu Sa’adah (Pusat Riset dan Inovasi Nasional, 2023)
Corporate strategy is a comprehensive or integrated strategy established based on the coordination of all areas within a company. The purpose of forming an organization is to achieve goals, whether for public or private organizations. This study aims to determine the corporate strategy of the state-owned enterprise Injourney (PT Aviasi Pariwisata Indonesia) Persero. Indonesian Journey or Injourney is a state-owned holding company in the aviation and tourism industry in Indonesia under the auspices of PT Aviasi Pariwisata Indonesia (Persero). The company's function is to conduct business activities as a holding company in the tourism and supporting industries. The research method used is a qualitative method with a literature analysis approach. The results of this study show that Injourney's corporate strategy in the tourism industry focuses on developing unique products and services, where market research can be conducted to understand the needs and references of consumers in tourism products and services, strengthening business networks to ensure high-quality products and services offered to consumers, strengthening the company's branding in the market by building a strong brand image, building good relationships with consumers, and developing innovation in tourism products and services.